Global Trend in the Research and Development of Acupuncture Treatment on Parkinson's Disease From 2000 to 2021: A Bibliometric Analysis - Li, Xiaoping; Wei, Wan; Wang, Yuan; Wang, Qiang; Liu, Zhibin (Frontiers in Neurology, 2022)
Background: Acupuncture has been widely used in the treatment of patients with Parkinson’s Disease (PD) in many countries. However, there is no bibliometric analysis of the global development of acupuncture on PD. Therefore, this study aimed to explore the current status and research trends of acupuncture on PD in recent 20 years by using CiteSpace (5.8.R3) and VOS viewer(1.6.14). Methods: Publications regarding acupuncture therapy for PD from 2000 to 2020 were extracted from the Web of Science database. CiteSpace and VOSviewer were used to analyze the number of publications, countries, institutions, journals, authors, references and keywords. Results: A total of 195 publications were retrieved from 2000 to 2020. The total number of publications fluctuated over the past 20 years, and reached the peak in 2020 with 31 publications. The country and institution contributing most to this field are the South Korea and Kyung Hee University, respectively. Hi-Joon Park was the most prolific author with 20 documents and 519 citations. The reference of Hi-Joon Park is also the one with the highest citation. Movement Disorders and Evidence Based Complementary and Alternative Medicine were the most popular journals in this field. “Electroacupuncture”, “Bee venom acupuncture” were on the list of the core keywords. Conclusion: The findings from this bibliometric study provide current status and trends in the research of acupuncture therapy on patients with PD over the past 20 years, which may help researchers identify hot topics and new directions for further researches in this field.